Conceptual physical science - Hewitt, Paul G; Suchocki, John; Hewitt, Leslie A (Boston : Addison-Wesley, 2012)
Conceptual Physical Science, Fifth Edition, takes learning physical science to a new level by combining Hewitt's leading conceptual approach with a friendly writing style, strong integration of the sciences, more quantitative coverage, and a wealth of media resources to help professors in class, and students out of class. It provides a conceptual overview of basic, essential topics in physics, chemistry, earth science, and astronomy with optional quantitative coverage. --
Keywords: Physical sciences -- Textbooks